Perceptions of Portuguese undergraduate students about assessment: a study in five public universities - Pereira, Diana (2017)
This paper draws upon a broader piece of research on assessment in higher education, particularly focusing on issues regarding the fairness and effectiveness of the assessment methods and their implications for the learning process. The perceptions of undergraduate students are analysed taking into account the effectiveness and fairness of both traditional and learner-centred assessment methods, as well their influence on the learning process. In total, 624 students participated in this study in five Portuguese Public Universities in different areas of knowledge and programmes. Data were collected through questionnaires. Findings suggest that assessment is seen as more effective and fairer when it is done through the use of learner-centred assessment methods rather than by traditional assessment (e.g. written tests or exams). The students also claim that they devote more time to study when assessment is performed through learner-centred assessment methods than by traditional ones. The most used assessment methods are written tests and oral presentations in group. However, differences in the programmes were identified as well as differences according to gender. Implications of the findings for assessment and for the teaching and learning process are discussed.